The physico-mechanical influence of dehydroxylized activated local kaolin: A supplementary cementitious material for construction applications. (June 2020) - Marfo, Kwame K.; Dodoo-Arhin, David; Agyei-Tuffou, Benjamin; Nyankson, Emmanuel; Obada, David O.; Damoah, Lucas N.W.; Annan, Ebenezer; Yaya, Abu; Onwona-Agyeman, B.; Bediako, Mark
Abstract: This work presents the effect of partially replacing metakaolin with Portland limestone cement to produce mortars for construction. Teleku Bokazo kaolin was explored as a SCM in the production of mortars. The hydration product between Portland limestone and metakaolin was studied. The kaolin was heat treated to form metakaolin and partially used to replace Portland limestone cement (PLC) in mortars to explore the optimum replacement and its mechanical and durability effect. The samples were characterized using X-ray diffraction (XRD) for phases and crystallinity of the kaolin. Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) gave information on the functional groups formed during the hydration and structure and surface morphology respectively. The pastes and mortars produced were subjected to setting time, water absorption, flexure and compression strength test. The mechanical properties were observed to increase with increasing metakaolin replacements. Therefore, from the results obtained, it is suggested that ∼20 % replacement of Portland limestone cement with Teleku Bokazzo metakaolin can be very suitable for construction applications.